2018
DOI: 10.1111/jfpp.13566
|View full text |Cite
|
Sign up to set email alerts
|

Omega fatty acids, phenolic compounds, and lipolysis of cheddar cheese supplemented with chia (Salvia hispanicaL.) oil

Abstract: Effect of supplementing cheddar cheese with chia oil on omega fatty acids, phenolic compounds, and lipolysis of cheddar cheese was investigated. Milk fat was partially replaced with chia oil, i.e., 2.5, 5, 7.5, and 10% (T1, T2, T3, and T4). Cheese prepared from 100% milk fat served as control, ripened at 6 °C for 90 days. Concentration of α‐linolenic acid in control and T3 was 0.51 and 12.55%. HPLC characterization revealed the concentrations of chlorogenic acid, caffeic acid, quercetin, phenolic glycoside‐k, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 44 publications
0
24
0
1
Order By: Relevance
“…The content of ALA increased from 0.5 to 12.5 per cent, while in 90 days ripened cheese, cholesterol concentration decreased from 119 to 92 mg/100 g, with lower concentration of organic acids. Chlorogenic acid, caffeic acid, quercetin, phenolic glycoside‐k and phenolic glycoside‐Q were 0.15, 0.26, 0.62, 1.55 and 1.97 mg/mL, respectively (Ullah et al , 2018). Health benefits associated with the consumption of fortified foods have been scientifically established, thereby increasing the demand for these foods throughout the world.…”
Section: Chia As a Food Fortificantmentioning
confidence: 99%
“…The content of ALA increased from 0.5 to 12.5 per cent, while in 90 days ripened cheese, cholesterol concentration decreased from 119 to 92 mg/100 g, with lower concentration of organic acids. Chlorogenic acid, caffeic acid, quercetin, phenolic glycoside‐k and phenolic glycoside‐Q were 0.15, 0.26, 0.62, 1.55 and 1.97 mg/mL, respectively (Ullah et al , 2018). Health benefits associated with the consumption of fortified foods have been scientifically established, thereby increasing the demand for these foods throughout the world.…”
Section: Chia As a Food Fortificantmentioning
confidence: 99%
“…To counteract this effect, some experiments have been performed to increase the n-3 fatty acid content offering fresh forage-based diets [10] or by implementing grazing feeding systems [3,4,11] to ruminants. Besides, the incorporation of seeds, microalgae [12], fish [13], and seed oil’s [14,15,16,17] supplements in the diet, has positively impacted n-3 fatty acid content of ruminants’ milk.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of secondary metabolites have been described for AF, e.g., quercetin, gallic acid (GA), catechin, and epicatechin [21,23]. These compounds are known as modulators of different physiological processes, as antioxidants, anti-inflammatory, and anti-bacterial properties [17,21,24]. We hypothesized that AF pods as supplement into the feed of dairy goats, increased the presence of bioactive compounds and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Milk fat replacement with vegetable oils has aimed to improve the fatty acid profile of cheese. Ullah et al (2018) fortified cheddar cheese with chia oil, finding a decrease in cholesterol content and an increase in ALA fatty acid. Regarding sensory quality, the authors found that there is an adequate acceptance of the fortified cheese compared to the unfortified product regarding odor and flavor attributes, when total cheese fat content is composed by 7.5% of chia oil and 92.5% of milk fat.…”
Section: Cheese Fortification By Direct Incorporation Of Oils and Oilmentioning
confidence: 97%
“…The use of dairy products as a means of transporting active compounds provides greater added value to its already recognized high nutritional quality (Lacroix et al, 2013). For example, several studies have been carried out fortifying different types of cheese by including vegetable oils in order to improve their nutritional quality by modifying their lipid profile (Achachlouei et al, 2013; Bermúdez-Aguirre & Barbosa-C anovas Gustavo V., 2011; Ullah et al, 2018). Through these fortified products, the consumption of UFA can increase preventing different diseases in the population such as CVD (Han et al, 2015).…”
Section: Cheese As a Food Matrix For The Ufa Inclusionmentioning
confidence: 99%